2020
DOI: 10.1038/s41467-020-19470-w
|View full text |Cite
|
Sign up to set email alerts
|

Predicting dwell fatigue life in titanium alloys using modelling and experiment

Abstract: Fatigue is a difficult multi-scale modelling problem nucleating from localised plasticity at the scale of dislocations and microstructure with significant engineering safety implications. Cold dwell fatigue is a phenomenon in titanium where stress holds at moderate temperatures lead to substantial reductions in cyclic life, and has been implicated in service failures. Using discrete dislocation plasticity modelling complemented by transmission electron microscopy, we successfully predict lifetimes for ‘worst c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(29 citation statements)
references
References 54 publications
4
25
0
Order By: Relevance
“…Due to the stress level being quite low to activate basal slip in this experiment, grains oriented favourably for prism slip systems were classified as 'soft' grains. Xu et al [7] suggested that the cold dwell fatigue and the dwell debit is sensitive to the dwell stress, which agrees well with the observations in this work. The origin of the dwell debit is the activation of slip systems, resulting in an accumulation of plastic strain during the stress dwell, which leads to load shedding from 'soft' grains to neighbouring 'hard' grains.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Due to the stress level being quite low to activate basal slip in this experiment, grains oriented favourably for prism slip systems were classified as 'soft' grains. Xu et al [7] suggested that the cold dwell fatigue and the dwell debit is sensitive to the dwell stress, which agrees well with the observations in this work. The origin of the dwell debit is the activation of slip systems, resulting in an accumulation of plastic strain during the stress dwell, which leads to load shedding from 'soft' grains to neighbouring 'hard' grains.…”
Section: Discussionsupporting
confidence: 93%
“…This is also confirmed by the increase of GND density in these grains as temperature rises and shown in Figure 11(i) and 11(j). GND densities at the grain boundaries were significantly higher than that within the grains, showing a dislocation pile-up [7,41] at the grain boundaries. For the rogue grain pair, the initial stress difference across the grain boundary increases slightly for T = 120 • C compared to room temperature, then drops at higher temperature.…”
Section: Load Sheddingmentioning
confidence: 91%
See 1 more Smart Citation
“…Dwell fatigue has been a vital issue for several decades in aeroengine industry as it significantly reduces the lifetime of titanium-based components [1][2][3][4]. It has been known that some dual-phase Ti alloys, for example Ti6242 and IMI685, are known as dwell sensitive, while others like Ti6246 are not [5][6], where this is potentially associated with the ratesensitive deformation behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the fatigue failure of the part was observed to be due to the creation of microvoids just before the failure. Xu et al (2020) used numerical and experimental methods to predict the dwell fatigue life of Ti834 titanium alloy using a discrete dislocation plasticity model. They investigated the effects of microstructure and its defects on the fatigue failure mechanisms that occurred on the parts representative of the jet engine spin test.…”
Section: Introductionmentioning
confidence: 99%